Hrvatske poslovice u slavenskome okruženju: određivanje hrvatskoga paremiološkog minimuma i optimuma - Varga, Melita Aleksa; Keglević, Ana (Slavia Centralis, 2020)
The present paper discusses the notion of Croatian proverbs, more precisely the steps that have been taken in an attempt to determine the Croatian paremiological minimum and optimum in the course of a project that started in 2014 by developing a part-text presentation questionnaire and conducting a field study with 867 participants from all major Croatian regions who filled in the first part of the most frequent proverbs found in the three major Croatian corpora. A second study was conducted in 2018 by using the same proverbs and resulted in 718 questionnaires filled out by Croatian participants, but this time they had to supply the second part of the proverb. The aim of this paper therefore is, a part from presenting a portion of the statistical results of the two surveys, to placing the issues regarding Croatian paremiology and the problems of determining the Croatian paremiological minimum/optimum into a wider Slavic context thus presenting similar attempts, methods and solutions in the Czech, Slovak, Slovene and Russian languages.
Keywords: paremiology; proverbs; Croatian; paremiological minimum; paremiological optimum